Understanding the role of epoxy resin and polyurethane in toughening metakaolin-based geopolymer matrix - Chen, Feng (2024)
Geopolymer is promising to replace cement, thus reducing the CO2 emissions of concrete production. However, the brittle behavior of geopolymer under bending loads limits its engineering applications. This work adopted epoxy resin and polyurethane modified epoxy resin (PMER) to synthesize the epoxy resin-PMER (EP) emulsion, which was further added into metakaolin-based geopolymer matrix for toughening. Moreover, the co-toughening mechanism of epoxy resin and polyurethane on metakaolin-based geopolymer was revealed based on the changes of major chemical bonds and Si binding energy of geopolymer before and after modification. The results show that the introduction of PMER does contribute to improve the flexural strength of geopolymer matrix by enhancing EP toughness. However, PMER also plays an adverse role in the Si-O-C bond generation of EP-modified metakaolin-based geopolymer (EMG), thus weakening the interconnections between 3D mesh structures inside EMG. A balance between these two contrasting effects is achieved when PMER content within EP reaches 60 wt%. At this time, the addition of 10 wt% EP can increase the flexural strength of metakaolin-based geopolymer matrix by 2.6 times.